2020
DOI: 10.1111/jocd.13811
|View full text |Cite|
|
Sign up to set email alerts
|

Retracted: The role of hyaluronic acid and amino acid against the aging of the human skin: A clinical and histological study

Abstract: Human skin, together with its undeniable protective role, performs the delicate task of mediating the metabolic and information exchanges between the body and the environment around it.Unfortunately, due to a series of exogenous (eg, ultraviolet radiation) and/or endogenous stressors (eg, endocrine-metabolic diseases) and aided by the inexorable flow of time, it may undergo a sequence of functional alterations and/or structural problems that could prejudice its integrity more or less seriously. 1 This leads to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(46 citation statements)
references
References 65 publications
0
44
0
2
Order By: Relevance
“…a Immediately after hyaluronic acid injection with anterior projection of the eyebrow emission of lamellar cytoplasmic prolongations and show aspects of nucleocytoplasmic activation constituted by a hypertrophy of the endoplasmic reticulum and of the Golgi complex [20,21]. The histological results in a previous study showed that this treatment is associated with an increase in collagen and hyaluronic acid that suggests a restoration of the cellular metabolism of the epidermis [22] Eyebrows play an important role in facial aesthetic perception [23], and their augmentation with HA filler is one technique for improving the facial appearance. Loss of various fat pad volumes and collagen in the dermis can create the appearance of eyebrow drooping.…”
Section: Discussionmentioning
confidence: 92%
“…a Immediately after hyaluronic acid injection with anterior projection of the eyebrow emission of lamellar cytoplasmic prolongations and show aspects of nucleocytoplasmic activation constituted by a hypertrophy of the endoplasmic reticulum and of the Golgi complex [20,21]. The histological results in a previous study showed that this treatment is associated with an increase in collagen and hyaluronic acid that suggests a restoration of the cellular metabolism of the epidermis [22] Eyebrows play an important role in facial aesthetic perception [23], and their augmentation with HA filler is one technique for improving the facial appearance. Loss of various fat pad volumes and collagen in the dermis can create the appearance of eyebrow drooping.…”
Section: Discussionmentioning
confidence: 92%
“…Hyaluronic acid (HA) is a linear polysaccharide present in the extracellular matrix of the skin. It is known to promote KC proliferation as well as elasticity regeneration, and it is used in dermatologic clinics as dermal fillers 59 . HA receptors are highly expressed on skin cells, as epidermal KCs and dermal fibroblasts contribute to antigen recognition by producing immune mediators and presenting antigens to local DCs 60 .…”
Section: Hyaluronic Acid Conjugatesmentioning
confidence: 99%
“…It is known to promote KC proliferation as well as elasticity regeneration, and it is used in dermatologic clinics as dermal fillers. 59 HA receptors are highly expressed on skin cells, as epidermal KCs and dermal fibroblasts contribute to antigen recognition by producing immune mediators and presenting antigens to local DCs. 60 HA is a hydrophilic molecule that also has a lipophilic patch domain, giving it an amphiphilic nature that allows it to diffuse through the SC.…”
Section: Noninvasive Transcutaneous Immunizationmentioning
confidence: 99%
“…Hyaluronic acid (HA) filler is an attractive substance to be used as filler, which is because of its features such as the ability to bind to large amounts of water and the natural presence of HA in the skin. It is synthesized on cell membrane of fibroblasts and keratinocytes, and also plays an important role in skin hydration facilitating cellular movement in inflammation and wound healing and its decrease is associated with skin aging [12,13]. HA injection was the second most popular nonsurgical cosmetic with a 60% increase from 2014 to 2018 and this could be explained by its affordability, minimal downtime, immediate results, minimal invasiveness and good safety profile, deriving from the feature that HA can be dissolved easily with hyaluronidase in case of complications [14].…”
Section: Introductionmentioning
confidence: 99%